The Role of Fintech: Financial Inclusion in MSME's: Case Study in Makassar City - Khairina Rosyadah; Budiandriani Budiandriani; Tasrik Hasrat (Jurnal Manajemen Bisnis, 2021)
The development of information technology which is supported by the rapid use of the internet has created several fintech that will make it easier for people to get digital financial services. The Financial Services Authority stated that the increase in national financial inclusion could be triggered by one factor, namely increased access to the use of fintech. The purpose of this study aimed to determine the role of fintech on financial inclusion in MSMEs in Makassar. The population in this study are MSMEs in Makassar with a sample of 335 informants. Researchers used primary data in the form of questionnaires that were distributed online and offline. Convenience sampling method is used in data collection in this type of quantitative research. Linear regression was used as an analytical technique. This study concluded that fintech has a positive effect on financial inclusion by 0,259.